2013
DOI: 10.4236/psych.2013.46076
|View full text |Cite
|
Sign up to set email alerts
|

Can Parenting Styles and Dimensions Questionnaire (PSDQ) Be Used in China?

Abstract: To evaluate the validity and reliability of the Chinese version of PSDQ (Parenting Styles and Dimensions Questionnaire, PSDQ). Method: 443 parents of children aged 6 to 16 who lived in Chongqing were selected. .52 of them were retested 6 weeks later in order to assess the retest reliability. Determination of reliability included: internal consistency: to calculate Cronbach coefficient; coefficient of retest reliability: to calculate person correlation of results in every subscale in twice measurements of 52 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 6 publications
2
11
0
Order By: Relevance
“…Similar steps of construct validity assessment were found in the Turkish validation study (Önder and Gülay 2009). However, criterion validity of PSDQ Bangla cannot be assessed because of the lack of culturally adapted instruments, which is supported by previous studies (Fu et al 2013;Arafat et al 2016Arafat et al , 2017Arafat 2016). The number of factors of the PSDQ Bangla based on eigenvalues obtained from PCA and a total of three factors were found, which is similar with the original scale (Robinson et al 1995).…”
Section: Forms Of Validitysupporting
confidence: 78%
See 2 more Smart Citations
“…Similar steps of construct validity assessment were found in the Turkish validation study (Önder and Gülay 2009). However, criterion validity of PSDQ Bangla cannot be assessed because of the lack of culturally adapted instruments, which is supported by previous studies (Fu et al 2013;Arafat et al 2016Arafat et al , 2017Arafat 2016). The number of factors of the PSDQ Bangla based on eigenvalues obtained from PCA and a total of three factors were found, which is similar with the original scale (Robinson et al 1995).…”
Section: Forms Of Validitysupporting
confidence: 78%
“…The number of factors of the PSDQ Bangla based on eigenvalues obtained from PCA and a total of three factors were found, which is similar with the original scale (Robinson et al 1995). Other validation studies also revealed similar three factorial structures, that is, authoritative, authoritarian, and permissive domain, which is also supported by Baumrind's ground work (Robinson et al 1995;Önder and Gülay 2009;Fu et al 2013;Olivari et al 2013;Kern and Jonyniene 2012;Morowatisharifabad et al 2016) LIMITATIONS: The evaluation of psychometric properties of the PSDQ Bangla revealed acceptable values that justify the scale to assess parenting style in Bangladesh. To the author's best knowledge, this is the first study to report on the psychometric properties of the Bangla version of PSDQ.…”
Section: Forms Of Validitysupporting
confidence: 67%
See 1 more Smart Citation
“…We assessed parenting styles using the modified 26-item PSDQ developed by Robinson et al (2001). This instrument is an appropriate measure of parenting among parents of preschool and school-age children (Robinson, Mandleco, Olsen, & Hart, 1995), exhibits internal consistency reliability for a sample of parents rearing preschool children in the United States (Winsler, Madigan, & Aquilino, 2005), and is a reliable and valid measure of parenting styles for parents in China (Fu et al, 2013). Authoritative parenting comprises three dimensions: (a) Warmth/Acceptance (seven items; e.g., “Expresses affection by hugging, kissing, and holding child”), (b) Reasoning/Induction (four items; e.g., “Talks it over and reasons with child when misbehaving”), and (c) Democratic Participation (four items; e.g., “Allows child to give input into family rules”; Wu et al, 2002, p. 485).…”
Section: Methodsmentioning
confidence: 99%
“…A review of this measure by Locke and Prinz (2002) recognized it as psychometrically justifiable in assessing child rearing and disciplining practices. It was also found to be age-appropriate for parents of preschoolers and school-age children, exhibiting an internal consistency reliability when measuring parents of preschoolers in the United States (Robinson et al, 1995) and in China (Fu et al, 2013). What's more, the measure was found to be reliable for maternal and paternal self-reported parenting styles of Chinese and Chinese immigrant parents (Chen et al, 2015), with Cronbach's alpha coefficients ranging from .59 to .72.…”
Section: Methodsmentioning
confidence: 96%